If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+7=6(7x-3)
We move all terms to the left:
9x+7-(6(7x-3))=0
We calculate terms in parentheses: -(6(7x-3)), so:We get rid of parentheses
6(7x-3)
We multiply parentheses
42x-18
Back to the equation:
-(42x-18)
9x-42x+18+7=0
We add all the numbers together, and all the variables
-33x+25=0
We move all terms containing x to the left, all other terms to the right
-33x=-25
x=-25/-33
x=25/33
| -1/8(y+2/5)=-3/4(y+1/6) | | 12+n=5-3 | | .52y+2.5=3.1 | | 13+p=6p-7 | | -1=-2/3x+1 | | 4-(6x+3)=12x+(2x+44) | | -x+41=-2(2-7x) | | 5x+1-1-25^x+10x-1=0 | | 8x+6-2x=6x+5 | | -x+41=-4-4x | | 5x-4=-4-3x | | 3x+46=124 | | 30x+25=-9^2 | | 3(x+1)=−2(x−1)+6 | | -36=-9x-3x | | 5x+1-1-25^x+10x+1=0 | | 4w²+19w-5=0 | | 5x-3(4x-5)-5=2x+4 | | (9D^2-12D+4)*y=0 | | (x+1)^2-4^2=(x-3)(x+5) | | 11x-8=8x+2 | | (9D^2-12D+4)y=0 | | r=−5r+18 | | 243^-y=(1/243)^3y*9^-2y | | 4(3x-1)+5x=2(x-3) | | E(x)=9x4+12x2+5 | | 4+4x=6x-18 | | 30x-7=-5 | | X2-6x=15 | | 9(s-3)=12s | | 16−5(x+9)2=0 | | (5x+1)+(6x+3)=180 |